Death, cemeteries and devotion: a material analysis of the phenomenon of popular saints based on images in Bauru and Jaú (São Paulo – Brazil): Morte, cemitérios e devoção: uma análise material do fenômeno dos santos populares em Bauru e Jaú (São Paulo – Brasil) a partir de imagens (Revista de História da UEG (REVHIST), 2021)
The phenomenon of popular saints is a characteristic feature of the Brazilian religiosity, multifaceted and plural. Popular saints are born in the cemetery through the spontaneous canonization undertaken by the local population, which sacralizes the individual who was ravaged by tragedy or had his life prematurely terminated. The social production of popular saints is linked to "marginal" devotion, that is, it is a process that recreates and readapts the precepts of the Catholic Church with subjects that would never be elevated to the rank of official saints. In this way, in the campo-Santo, the deceased and the grave are objects of veneration. Therefore, in order to understand the materiality and the liveliness of the cult of popular saints, this paper proposes to analyze two cemetery saint deposits, one in the city of Bauru, and the other in the city of Jaú. Thus, through a qualitative approach with documentary and bibliographical research instruments, it is intended to study the influence of the sacred in the popular imaginary from the Local and Regional History approach, relating the popular saints to the memory of the selected cities. The historical source used will be archeological, including the tombs of local saints. These will be analyzed in iconographic elements, in order to identify material and symbolic aspects that differentiate them from other graves in the necropolises.Keywords: Popular saints. Cemeteries. Devotional deposits. Sacred. Profane.